Sex differences in mechanical allodynia: how can it be preclinically quantified and analyzed? - Nicotra, Lauren; Tuke, Jonathan; Grace, Peter; Rolan, Paul E.; Hutchinson, Mark R. (Frontiers in Behavioral Neuroscience, 2014)
Translating promising preclinical drug discoveries to successful clinical trials remains a significant hurdle in pain research. Although animal models have significantly contributed to understanding chronic pain pathophysiology, the majority of research has focused on male rodents using testing procedures that produce sex difference data that do not align well with comparable clinical experiences. Additionally, the use of animal pain models presents ongoing ethical challenges demanding continuing refinement of preclinical methods. To this end, this study sought to test a quantitative allodynia assessment technique and associated statistical analysis in a modified graded nerve injury pain model with the aim to further examine sex differences in allodynia. Graded allodynia was established in male and female Sprague Dawley rats by altering the number of sutures placed around the sciatic nerve and quantified by the von Frey test. Linear mixed effects modelling regressed response on each fixed effect (sex, oestrus cycle, pain treatment). On comparison with other common von Frey assessment techniques, utilizing lower threshold filaments than those ordinarily tested, at 1 second intervals, ¬¬appropriately and successfully investigated female mechanical allodynia, revealing significant sex and estrus cycle difference across the graded allodynia that other common behavioral methods were unable to detect. Utilising this different von Frey approach and graded allodynia model, a single suture inflicting less allodynia was sufficient to demonstrate exaggerated female mechanical allodynia (N1S3, t = 3.4; N3S1, t = 7.7) throughout the phases of dioestrus (t = 3.3) and pro-oestrus (t = 3.5). Refining the von Frey testing method, statistical analysis technique and the use of a graded model of chronic pain, allowed for examination of the influences on female mechanical nociception that other von Frey methods cannot provide.